Redundant and Diversified Roles Among Selected Arabidopsis thaliana EXO70 Paralogs During Biotic Stress Responses - Pečenková, Tamara; Potocká, Andrea; Potocký, Martin; Ortmannová, Jitka; Drs, Matěj; Janková Drdová, Edita; Pejchar, Přemysl; Synek, Lukáš; Soukupová, Hana; Žárský, Viktor; Cvrčková, Fatima (Frontiers in Plant Science, 2020)
The exocyst heterooctameric vesicle-tethering complex is important for plant development, growth and immunity. Multiple paralogs exist for most subunits of this complex; especially the membrane-interacting subunit EXO70 underwent extensive amplification in land plants, suggesting functional specialization. Despite this specialization, most Arabidopsis exo70 mutants are viable and free of developmental defects, probably as a consequence of redundancy among isoforms. Our in silico data-mining and modelling analysis, corroborated by transcriptomic experiments, pinpointed several EXO70 paralogs to be involved in plant biotic interactions. We therefore tested corresponding single and selected double mutant combinations (for paralogs EXO70A1. B1, B2, H1, E1 and F1) in their two biologically distinct responses to Pseudomonas syringae, root hair growth stimulation and general plant susceptibility. A shift in defence responses toward either increased or decreased sensitivity was found in several double mutants, compared to wild type plants or corresponding single mutants, strongly indicating both additive and compensatory effects of exo70 mutations. Our analysis uncovers that there is less of functional redundancy among isoforms than we could suppose from whole sequence phylogeny, and that even paralogs with overlaping expression pattern and similar membrane-binding capacity appear to have exclusive roles in plant development and biotic interactions.